Degradation of forests Due to Fallacious Yield Regulation and Harvesting: a Case Study from Vyara forest Division of Gujarat, India - Verma, A. K. (Indian Forester, 2002)
Independent India inherited large areas of over-exploited forests. The reasons for over-exploitation were chiefly the indiscriminate felling of trees during war time, the over-exploitation by the rulers of the Princely States and the purely commercial outlook towards forest resources. Although, this was realised even during the early years of independence, forests continued to degrade due to the inadequate attention paid in restocking the forests and ineffective measures in controlling biotic interferences. It is also worth nothing that the forest degradation was more due to over-exploitation by authorised agencies than due to illicit cutting of trees for timber and firewood. These aspects are discussed in this paper using data from Vyara Forest Division of Gujarat State in India. Although the Vyara forests were managed under a Working Plan, the annual yield realised considerable exceeded the estimated value. This fact calls for the need for implementing Working Plan prescriptions in its entirety and not by parts. Further, there is a need to find out ways and means of volumetric control or numeric restrictions on fellings in all silvicultural systems. An analysis of the functioning of the Forest Labourers Co-operative Societies revealed that their role in forest conservation is questionable. Most often, the societies are mismanaged and represented by a small group of profit seekers who do not care for forest conservation. It is concluded that managerial inadequacies and greed of harvesting agencies are major factors contributing to forest degradation.